PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN YANG DIMODERASI OLEH STRUKTUR KEPEMILIKAN - Gunawan, Barbara; Yuanita, Riska (Universitas Muhammadiyah Surakarta, 2018)
The research aimed at analyzing the influence of corporate social responsibility towards the financial performance moderated by foreign ownership in mining companies registered in Indonesian Stock Exchange in 2012- 2015. The subjects of the research were mining companies with 8 samples of 32 companies selected by using purposive sampling method. The analysis tool used was Moderator Regression Analysis (MRA).Â The research used double regression analysis to test whether or not corporate social responsibility had positive influence towards return on equity, economic value added, and net profit margin. The research also used simple regression analysis to test whether or not foreign ownership moderates the relationship between corporate social responsibility and financial performance. The result of the research showed that corporate social responsibility had a significant influence towards return on equity, economic value added, and net profit margin. However, foreign ownership did not moderate the relationship between corporate social responsibility and financial performance.